2015
DOI: 10.3389/fnhum.2015.00317
|View full text |Cite
|
Sign up to set email alerts
|

Estimating frontal and parietal involvement in cognitive estimation: a study of focal neurodegenerative diseases

Abstract: We often estimate an unknown value based on available relevant information, a process known as cognitive estimation. In this study, we assess the cognitive and neuroanatomic basis for quantitative estimation by examining deficits in patients with focal neurodegenerative disease in frontal and parietal cortex. Executive function and number knowledge are key components in cognitive estimation. Prefrontal cortex has been implicated in multilevel reasoning and planning processes, and parietal cortex has been assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 75 publications
(88 reference statements)
2
15
0
Order By: Relevance
“…Also in these area the neural activity appears to be correlated either to the probability of movement in a given direction or to the marginal magnitude of the expected reward (Salzman et al, 2005 ; Hikosaka et al, 2006 ). In the present study we observed a large activation of right lateral prefrontal cortex, which is generally associated with probability estimation of different (relative) values assigned to the expected reward for each possible choice (Platt and Glimcher, 1999 ; Poldrack et al, 1999 ; Weickert et al, 2009 ; d'Acremont et al, 2013 ; Bisbing et al, 2015 ). The lateral prefrontal area is generally involved in cognitive control that allows information processing and behavior to vary adaptively from moment to moment depending on current goals.…”
Section: Discussionsupporting
confidence: 49%
“…Also in these area the neural activity appears to be correlated either to the probability of movement in a given direction or to the marginal magnitude of the expected reward (Salzman et al, 2005 ; Hikosaka et al, 2006 ). In the present study we observed a large activation of right lateral prefrontal cortex, which is generally associated with probability estimation of different (relative) values assigned to the expected reward for each possible choice (Platt and Glimcher, 1999 ; Poldrack et al, 1999 ; Weickert et al, 2009 ; d'Acremont et al, 2013 ; Bisbing et al, 2015 ). The lateral prefrontal area is generally involved in cognitive control that allows information processing and behavior to vary adaptively from moment to moment depending on current goals.…”
Section: Discussionsupporting
confidence: 49%
“…It also remains important to establish whether the CET is a test sensitive and specific to frontal lobe damage. It has been reported that CET performance is impaired in a variety of neurological conditions such as stroke ( Shoqeirat et al, 1990 ), Alzheimer's disease ( Della Sala et al, 2004 ), frontotemporal dementia and corticobasal syndrome ( Bisbing et al, 2015 ), Korsakoff's syndrome ( Brand et al, 2003 ), Huntington's disease ( Brandt et al, 1988 ) and traumatic brain injury ( Schretlen, 1992 ) and psychiatric conditions such as schizophrenia (e.g., Roth et al, 2012 ; Gansler et al, 2014 ). However, these studies do not allow us to determine whether the CET is a test specific to frontal lobe damage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CET performance involves numerical competence19, we choose to include a non-symbolic comparison task because it can easily administered across age groups, is not contingent on school curriculum and is related to math performance20.…”
Section: Methodsmentioning
confidence: 99%